Proficiency in oocyte retrieval: how many procedures are necessary for training? - Goldman, Kara N (2011)
OBJECTIVE: To determine a minimum number of procedures required for proficiency in oocyte retrieval and to characterize skill acquisition. DESIGN: Retrospective analysis. SETTING: Reproductive Endocrinology and Infertility fellowship training program. STUDY SUBJECTS: Fellows in training from 2005-2007 and 2008-2010. INTERVENTIONS: None. MAIN OUTCOME MEASURES: Proficiency scores (PS) were calculated by dividing the number of oocytes retrieved by oocytes expected (PS=oocytes retrieved/expected). 2005-2007 trainees were grouped and proficiency scores calculated as an average during specific points in their training. 2008-2010 trainees were compared individually to determine differences in individual skill acquisition. RESULTS: A greater number of oocytes were retrieved than expected, 8.6 vs. 7.6 (p <0.05). A relatively lower proficiency score (PS) was noted during the first 10 trainee aspirations (PS=1.1) compared to subsequent aspirations (PS=1.25 retrievals 11-20, PS=1.21 retrievals 21-30 and >31). When individual fellows’ scores were calculated, the majority achieved proficiency by 20 aspirations and all but one trainee achieved the mean staff PS by 50 retrievals. CONCLUSIONS: Regardless of a trainee’s initial proficiency in oocyte retrieval, there are no statistically significant differences in the learning curve between trainees. The majority of individual fellows in training demonstrate proficiency in follicular aspirations within 20 procedures; however, a minority may require 50 procedures to achieve the proficiency of an attending physician. CAPSULE: The majority of fellows in training demonstrate proficiency in follicular aspirations within 20 procedures; however, a minority may require 50 procedures to achieve the proficiency of an attending physician.